A Inventarisasi Arthropoda dan Tingkat Serangan Hama pada Teknik Budidaya Padi (Oryza sativa L.) di Desa Bumi Agung Kecamatan Lempuing: Inventory of Arthropoda and Pest Attack Rate on Rice (Oryza Sativa L.) Cultivation Techniques in Bumi Agung Village Lempuing Sub-District - Bambang Gunawan; Arsi Arsi; Indah Anisyatulusna (Politeknik Negeri Lampung, 2022)
Rice (Oryza sativa L.) is one of important crops in current era because the crop produce staple food for more than half of world population. Rice cultivation has been facing many obstacles to reach the expected yield. One the causes is the attack of rice pests causing damages on vegetative and generative stages of the crop, and these would lead to yield reduction. The purpose of this research was to determine the method of cultivating rice plants and arthropods and the level of pest attack. This research was carried out in May 2021 with a survey method on five different rice fields in Bumi Agung Village by interviewing farmers to obtain information about farmers' behavior in rice cultivation and observing insect pests in rice plantations. The results obtained from field practice were the discovery of three pests in rice plants, namely Oxya chinensis, Acrida cinerea, dan Atherigona sp. The control carried out by farmers in controlling pest attacks is in the form of jajar legowo, technical culture such as land management, fertilization, weeding and others which are included in integrated pest control (IPM).From the observational data analyzed that the application of integrated pest control (IPM) has proven to have an impact on reducing pest attacks where out of 5 paddy fields that were observed, the 5th land belonging to Mr. Agus was found to have few insect pests and weeds in his rice fields with an average of 0%.